Solvent-Controlled Cascade Reaction of Ugi/Pd-Catalyzed Intramolecular Divergent C-H Functionalization for Regioselective Synthesis of Cyclopropanated N-Heterocycles. (October 2019) - Shang, Tianyi; Pan, Yan; Chen, Zhong; Yang, Junjie; Guo, Xinling; Guo, Leilei; Liu, Yan
Abstract: A novel cascade reaction of Ugi/Pd-catalyzed intramolecular divergent C-H functionalization, which is controlled by solvent effect to achieve the regioselective synthesis of spiro- and fused-cyclopropanated indolines from the Ugi adduct of N -acylated 2-bromoarylamides.